Elaborasi Etnomatsains Rumah Adat Mbaru Niang dalam Upaya Peningkatan Eduwisata Masyarakat Wae Rebo - Anggraini, Vidia Dwi; Anarky, Fajar Gempur; Fariha, Hayyin; Safitri, Andini; Setiawan, Windi (Program Studi Pendidikan Matematika, 2023)
Ethnomatsains learning is a learning innovation that combines local culture with Math and Science materials. This study aims to analyze the social functions and concepts of Mathematics and Science in improving edu-tourism in the Mbaru Niang Traditional House, Wae Rebo community. The method used is descriptive research with a qualitative approach, with the Wae Rebo community as the research subject and Mbaru Niang Traditional House as the research object. Data was collected through interviews, documentation, and literature study. Through this research, it was found that there are many Math and Science concepts associated with the Mbaru Niang Traditional House in terms of the house and the surrounding environment. The main social function of the Mbaru Niang Customary House is the difference in status between the original customary house at the top and the houses below it owned by the Wae Rebo community. Although they do not live together, cooperation is maintained. This research proves that Ethnomatsains can contribute to improving edu-tourism and enriching learning by collaborating local culture with Math and Science lessons.